Introductory word : FUSILLI: research through the lens of one's own experience during the war - Muradyan Olena, (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2023)
The official title in English is «Fostering the Urban food System Transformation through Innovative Living Labs Implementation». The research and innovation program of the European Union «Horizon 2020» H2020-CE-FNR-07-2020 in accordance with the grant agreement №101000717 finances the project. Official website of the project: www.fusilli-project.eu